Blue light irradiation combined with low-temperature storage further enhances postharvest quality of strawberries through improving antioxidant defense and cell wall metabolic activities - Wei Lu; Wanqing Li; Keke Zhao; Xiaofeng Bai; Yuchang Zhang; Qingyun Li; Zhanjun Xue; Xin-Xin Wang (Food Chemistry: X)
Few studies have explored the impact of blue light-emitting diode (BL) irradiation combined with different storage temperatures on antioxidant defense and cell wall metabolic activities related to the quality deterioration of postharvest strawberries. This study investigates the effects of BL exposure as a non-chemical preservation strategy to improve the postharvest quality of strawberries stored at 22 °C and 8 °C. Over a 10-day storage period, BL irradiation significantly reduced respiratory and ethylene production rates, while preserving fruit firmness and increasing the contents of soluble sugar and total phenol at both temperatures. Additionally, increases of the enzymatic activities of antioxidant defense metabolism (e.g. superoxide dismutase (SOD) and peroxidase (POD)) accompanied with decreased levels of reactive oxygen species (ROS) (e.g. superoxide anion (O2−), and hydrogen peroxide (H2O2)) and the content of secondary metabolites (e.g. ascorbic acid (AsA)) accompanied with enhanced activities of ascorbate peroxidase (APX) and glutathione reductase (GR) were found in BL irradiated postharvest strawberries at the later stages of storage. Meanwhile, BL irradiation also mitigated the activity of cell wall-degrading enzymes, thereby reducing the degradation rates of protopectin (PP), cellulose (CEL), and hemicellulose (HCEL), while maintaining the structural integrity of cell walls. According to fuzzy mathematics analysis, the membership function values for BL irradiated postharvest strawberries at different storage temperatures ranked as follows: BL + 8 °C (0.60) > BL + 22 °C (0.52) > 8 °C (0.46) > 22 °C (0.36). These findings suggest that BL irradiation not only extends the shelf life of strawberries by modulating antioxidant defense and cell wall metabolic activities but also maintains their commercial quality, particularly under low-temperature storage conditions. Therefore, BL irradiation holds significant promise for minimizing quality deterioration in postharvest strawberries during cold storage.